Conventional and Molecular Identification of Culturable Airborne Bacteria (Plant Tissue Culture and Biotechnology, 2020)
Bacteria isolated from the environment during the present study were representative of normal microflora of the skin, respiratory and urinary tracts; it also includes some soil and water-borne pathogenic and nonpathogenic genera. Six samples from different locations were studied for bacterial investigation. Among 14 isolates obtained, 13 were Gram positive, and the rest one was Gram negative. Out of 13 Gram positive isolates, 12 were round-shaped non spore forming and were identified as Planococcus citreus, Stomatococcus mucilaginosus, Kocuria kristinae, Micrococcus agilis (2), Kytococcus sedentarius (2), Micrococcus luteus, Micrococcus lylae and M. roseus, Staphylococcus aureus, Staphylococcus epidermidis and rod-shaped non spore forming identified as Renibacterium salmoninarum. The Gram-negative bacteria was identified as Pseudomonas aeruginosa. Other than provisional identification, two isolates (JG 40 and SG 49) were further confirmed through molecular characterization on the basis of 16Sr RNA gene sequence analysis as Staphylococcus aureus and Pseudomonas aeruginosa repectively. Spearman’s correlation showed that air temperature and wind speed negatively correlated with the bacterial abundance. It is clear that none of the samples containing airborne pathogens collected was safe for human health due to presence of potentially pathogenic microorganisms. Many were human pathogenic as well as food poisoning microorganisms.Plant Tissue Cult. & Biotech. 30(1): 15-25, 2020 (June)